2020
DOI: 10.3390/drones4040072
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among Earthwork and Cropmark Anomalies within Archaeological Landscape Investigation by Using LiDAR and Multispectral Technologies from UAV

Abstract: This project aimed to systematically investigate the archaeological remains of the imperial Domitian villa in Sabaudia (Italy), using different three-dimensional survey techniques. Particular attention in the research was paid to the identification and documentation of traces that buried structures left on the surface occupied by the villa, which extended for 46 hectares, an area that was fully covered with structures. Since a dense pine forest was planted during the 1940s and is currently covering the site, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This may be due to the fact that they are underground anomalies or have been backfilled (in the case of concave-shaped remains) or eroded (in the case of convex-shaped remains) over time. Examples of (B) include human remains and clandestine mass graves (if no burial mounds are visible on site) [ 45 , 46 ] or other buried historical evidence like earthwork anomalies [ 13 ] and remains of objects embedded in the ground [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the fact that they are underground anomalies or have been backfilled (in the case of concave-shaped remains) or eroded (in the case of convex-shaped remains) over time. Examples of (B) include human remains and clandestine mass graves (if no burial mounds are visible on site) [ 45 , 46 ] or other buried historical evidence like earthwork anomalies [ 13 ] and remains of objects embedded in the ground [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Ronchi et al [ 13 ] showed that LiDAR outperforms RGB or multispectral approaches in the context of terrain anomaly identification. A LiDAR system generally consists of a single-wavelength laser that typically operates at a near-infrared wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of UAV and LiDAR provides excellent data [21]. Data from LiDARs are able to produce earthworks information [119], whereas images from UAVs provide a clear picture of the study area [120,121]. Apart from that, the issue of limited budget allocation is raised in the small and medium-scale designs for using airborne LiDAR [19].The use of UAVs is considered as another good alternative for this situation [122].…”
Section: Limitationsmentioning
confidence: 99%
“…To the best of the authors' knowledge, the only multirotor UAS capable of flying for more than 60 min, thanks to an exquisite aerodynamic design, a light carbon-fibre cell and the use of Lithium-Ion cells, is CONDOR™, manufactured by the Spanish company Dronetools™ (Gelves-Seville) [7] Although a maximum flight time on the verge of an hour for a multirotor UAS is an exceptional achievement, it is clearly not sufficient when reasonably large payloads, such as Light Detection and Ranging Systems (LiDAR), must be used [8], or when lower weight payloads are installed but the operation involves the inspection of large expanses of terrain [9][10][11]. The market for H-UAS and hybrid generators is very limited.…”
Section: Introduction and Review Of The Main Hybrid Generators Available In The Marketmentioning
confidence: 99%